ASPECT scores of patients with focal intracerebral hemorrhage were correlated with their short- and medium-term functional outcomes. (2nd December 2021) - Zheng, Qiuyue; Liu, Xiaojie; yan, Ke; He, Liang; Chen, Yingzhu
ABSTRACT: Purpose: The Alberta Stroke Program Early CT Score (ASPECTS) is widely used to guide thrombolytic therapy and predict the functional outcome of patients with acute ischemic stroke (AIS). Whether ASPECTS can predict the functional outcome of patients with intracerebral hemorrhage (ASPECTS-H) remains unclear. Methods: Patients with primary intracerebral hemorrhage (ICH) were collected and retrospectively analyzed. ASPECTS-H was assessed at admission. Patients were followed up at 30 days and 90 days after the onset of ICH. Occurrence of death within 90 days after ICH was the primary endpoint. Modified Rankin Scale (mRS) ≥ 3 was considered a poor functional outcome. Results: A total of 149 patients met eligibility criteria; 61 (40.9%) had poor functional outcome at 30 days, and 37 (24.8%) had poor functional outcome at 90 days. Using binary logistic regression modeling, we found that a low ASPECTS-H was associated with a poor functional outcome. The risk ratio of a low ASPECTS-H was 2.31 at 30 days ( P = 0.000; 95% CI, 1.560–3.421) and 2.711 at 90 days ( P = 0.000; 95% CI, 1.677–4.381). The optimal cutoff value of ASPECTS-H to discriminate good and poor 30-day and 90-day outcomes was 7.5 (Sensitivity30-day = 0.636, 1-Specificity30 – day = 0.311; Sensitivity90-day = 0.580, 1-Specificity90-day = 0.270). Conclusions: A low ASPECTS-H was an indicator of poor short-term and long-term functional outcomes of ICH.